HUBUNGAN PENGETAHUAN DAN KEPATUHAN IBU HAMIL DALAM MENGKONSUMSI TABLET TAMBAH DARAH TERHADAP KEJADIAN ANEMIA - Ismiati (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
Problems related to maternal health that can cause death include post-partum hemorrhage, including those caused by anemia. Factors that influence the incidence of anemia are related to maternal knowledge and compliance. Objective: this research is to determine the relationship between knowledge and compliance of pregnant women in consuming Fe tablets with the incidence of anemia in the Dompu Barat Health Center Work Area in 2023. Method: This research uses a quantitative type of research using the Descriptive Analytical method. Sampling in this study used the Simple Random Sampling method, the number of samples in this study was 47 samples of pregnant women. Statistical tests use the Chi Square Test. Results: Research shows that there is a relationship between knowledge and compliance of pregnant women in consuming blood supplement tablets on the incidence of anemia with a P-Value of 0.000 or p ɑ 0.05. then Ha is accepted and Ho is rejected. Conclusion: There is a relationship between knowledge and compliance of pregnant women in consuming blood supplement tablets on the incidence of anemia.